2004
DOI: 10.1002/chin.200408320
|View full text |Cite
|
Sign up to set email alerts
|

New Antimalarial Drugs

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
83
0
6

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(89 citation statements)
references
References 1 publication
0
83
0
6
Order By: Relevance
“…Some drugs are currently available, alone or in association with other antimalarials (Wiesner et al, 2003;Baird, 2005), but the development of new molecules remains a priority in the absence of an efficient vaccine strategy.…”
mentioning
confidence: 99%
“…Some drugs are currently available, alone or in association with other antimalarials (Wiesner et al, 2003;Baird, 2005), but the development of new molecules remains a priority in the absence of an efficient vaccine strategy.…”
mentioning
confidence: 99%
“…Approximately 40% of the world population lives at risk of this disease and this constitutes a large burden on the health and economic development of low-incomes countries [1][2][3]. Although the World Malaria Report 2011 showed that there has been significant and durable progress in battling this disease, emergence of parasite resistance to antimalarial medicines remains a threat to this continued stride toward the reduction of malaria cases in the world.…”
Section: Introductionmentioning
confidence: 99%
“…Estimates range from 300 to 500 million clinical cases of malaria each year and approximately 1.5-2.5 million die due to non-availability of a proper therapeutic agent [1][2][3] . During the past four decades, chloroquine (CQ) and other aminoquinolines have been the mainstays of malarial chemotherapy due to their therapeutic efficacy 4 .…”
Section: Introductionmentioning
confidence: 99%